2022
DOI: 10.1002/pi.6478
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of star‐shaped architecture and poly(ethylene glycol) moieties on poly(lactic acid) stereocomplex crystallization behaviors

Abstract: Stereocomplex (sc) crystal formation represents an important strategy to improve the physical properties of poly(lactic acid) (PLA), including enhanced thermal resistance, anti‐hydrolysis and mechanical performance. Therefore, understanding and controlling the sc crystallization behaviors is an important and widely studied research topic. Herein, we investigate the cooperative effect of star‐shaped PLA chain topology and poly(ethylene glycol) incorporation on sc formation. We synthesize a series of poly(lactid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In addition, the driving force of the stereocomplex between OLLA and ODLA may be correlated with the hydrogen bond formation between CH 3 and CO. By comparing the CO and CH 3 stretching vibration peaks of OLLA, ODLA, and SC‐OLA‐MPs, it was found that the characteristic peak of CO was shifted from 1748 to 1744 cm −1 and the location of the CH 3 stretching vibration peak also showed the same trend from 2997 to 2991 cm −1 , which was because of the formation of a large number of hydrogen bonds between the molecular chains of OLLA and ODLA, and the density of electron clouds around the functional groups decreased, thus reducing their stretching vibration frequencies and increasing the growth of chemical bonds, resulting in the migration of the stretching vibration peaks of SC‐OLA‐MPs to lower wave numbers 27 …”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…In addition, the driving force of the stereocomplex between OLLA and ODLA may be correlated with the hydrogen bond formation between CH 3 and CO. By comparing the CO and CH 3 stretching vibration peaks of OLLA, ODLA, and SC‐OLA‐MPs, it was found that the characteristic peak of CO was shifted from 1748 to 1744 cm −1 and the location of the CH 3 stretching vibration peak also showed the same trend from 2997 to 2991 cm −1 , which was because of the formation of a large number of hydrogen bonds between the molecular chains of OLLA and ODLA, and the density of electron clouds around the functional groups decreased, thus reducing their stretching vibration frequencies and increasing the growth of chemical bonds, resulting in the migration of the stretching vibration peaks of SC‐OLA‐MPs to lower wave numbers 27 …”
Section: Resultsmentioning
confidence: 71%
“…As shown in Figure 8, the crystallinity versus time showed an “S” curve 27 . The crystallization process of the sample can be divided into three stages: the induced crystallization period, the middle crystallization period, and the late crystallization period.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Figure 4f, the diffraction peaks of PLA at 14.8°, 16.6°, 19.0°, and 22.3°w ere assigned to (010), (110)/(200), (203), and (015) crystal planes of α-form homocrystallites, respectively. 54 Notably, after degradation, there was a significant decrease in the intensity of these characteristic peaks, indicating that these crystalline planes of PLA were disrupted by enzymatic digestion.…”
Section: ■ Results and Discussionmentioning
confidence: 98%